Evaluation of sodium alendronate activity on bone repair under hormones absence - Machado, Ana Lourdes da Silva; Monteiro da Silva, Claudia Maria de Oliveira; Brandão, Adriana Aigotti H.; Arisawa, Emília Angela Loschiavo; Rocha, Rosilene Fernandes da (Brazilian Dental Science, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0cm; padding-left: 0cm; padding-right: 0cm; border-top: windowtext 1.5pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div;"> This research proposes to study sodium alendronate effect on bone repair of ovarectomized rats. Thirty-six adult rats were ovariectomized and distributed in four groups, with nine rats in each group. A surgical defect was performed in one tibia of each animal. The control group received only water "ad libitum" and the three experimental groups received sodium alendronate diluted in the drinking water in the doses of 0.25 mg/kg; 0.5 mg/kg e 0.75 mg/kg, respectively. Three animals of each group were sacrificed after three, seven and 14 days. The histhologic analysis of the tibia material showed a more marked bone deposition in the groups treated with higher doses of sodium alendronate. The most mature bone repair process was observed in the 14-days/0.5 mg/kg group, with bone spindles and remodeling in a higher degree of development, showing a dose-dependency regarding sodium alendronate.